Cortical plasticity and levodopa-induced dyskinesias in Parkinson's disease: Connecting the dots in a multicomponent network. Issue 6 (June 2017) - Rajan, Roopa; Popa, Traian; Quartarone, Angelo; Ghilardi, Maria Felice; Kishore, Asha
Highlights: Plasticity in the motor network is impaired in Parkinson's disease with dyskinesias. In an interconnected network, dysfunction of a node affects brain plasticity downstream. The cerebellum as a sensorimotor integrator is a key player in this multicomponent network. Abstract: Levodopa-induced dyskinesias are motor complications following long term dopaminergic therapy in Parkinson's disease (PD). Impaired brain plasticity resulting in the creation of aberrant motor maps intended to encode normal voluntary movement is proposed to result in the development of dyskinesias. Traditionally, the various nodes in the motor network like the striato-cortical and the cerebello-thalamic loops were thought to function independent of each other with little communication among them. Anatomical evidence from primates revealed the existence of reciprocal loops between the basal ganglia and the cerebellum providing an anatomical basis for communication between the motor network loops. Dyskinetic PD patients reveal impaired brain plasticity within the motor cortex which may be modulated by cortico-cortical, cerebello-cortical or striato-cortical connections. In this article, we review the evidence for altered plasticity in the multicomponent motor network in the context of levodopa induced dyskinesias in PD. Current evidence suggests a pivotal role for the cerebellum in the larger motor network with the ability to integrate sensorimotor information and independently influence multiple nodes in this network. Targeting the cerebellum seems to be a justified approach for future interventions aimed at attenuating levodopa-induced dyskinesias.